Role of project governance in managing projects sustainability: A theoretical perspective - Ullah, Mehfooz; Khan, Muhammad Waris Ali; Lee, Chia Kuang (Springer Singapore, 2021)
Sustainability is incessantly posing challenges when it is studied juxtaposition with project management. To ensure sustainability companies undertaking projects ought to set strategic and operational plans that will add to the project sustainability. Research shows that existing project management structures do not effectively consider sustainability issues and therefore need revisions at strategic and operational levels. Similarly, while the theme of project governance is finding traction in the literature, the discussion that connects project governance and sustainability in projects is elusive. This research work is specifically focusing on developing a linkage between project governance and managing sustainability in projects. There is an acute scarcity of literature encircling linkage between project governance and sustainable project management, thus, based on the extensive review of the literature, this study is one of the pioneering studies to highlight the relationship between the themes of project governance and sustainable project management.